KORELASI MINAT MEMBACA DENGAN KETERAMPILAN MENULIS PUISI - Nursalamah, Rita; Hasim, Abdul; Nurwahidah, Lina Siti; Kartini, Ari (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study entitled "Correlation of Reading Interest with Poetry Writing Skills". Lack of students' skills in writing poetry is the background of this research. The facts show that the test scores on poetry writing competence are low, the number of book borrowers is low, and students' interest in reading is low. This condition is a challenge for teachers so that students master the material being taught by achieving KKM. The method used in this study is descriptive correlational using quantitative. It intends to describe the relationship between writing poetry and students' reading scores. The population in this study were all class VIII students at SMPN 1 Selaawi Garut for the 2021/2022 academic year, which consisted of 11 classes. The sample used was taken randomly from each class, namely three people per class. If the total sample in this study is 33 students. The results obtained are as follows. First, an overview of the interest in reading of Class VIII students of SMP Negeri 1 Selaawi Garut for the 2021/2022 academic year, namely 8 students (24%) are in the high category, 17 students (51%) are in the medium category, and 8 students ( 24%) are in the low category. Second, an overview of students' poetry writing skills, namely 18 students (18%) are in the high category, 27 students (82%) are in the medium category. Third, there is a significant relationship between reading interest and students' poetry writing skills based on the r test of 0.8, which means very strong. The implications of this research are expected to be used as a reference for teachers in learning to write poetry.